'Every nation who dwells in the land': Latter-day Saint Internationalisation, sacralising spaces, and the Hill Cumorah Pageant. Issue 2 (2nd April 2020) - Dunstan, Adam
ABSTRACT: In 2018, the Church of Jesus Christ of Latter-day Saints announced the end of the Hill Cumorah Pageant, a seemingly minor policy decision which, I argue, reflects major changes in how a faith which has earnestly sought to present itself as mainstream American in the twenty-first century is attempting to reconfigure itself in the twenty-first century. Drawing on ethnographic research, I argue that the Hill Cumorah Pageant (an outdoor production on the hill) utilises discursive and spatial practices which connect a specific version of the Book of Mormon 'Promised Land' narrative to the US via a process of spatially anchoring the Book of Mormon landscape and establishing continuity between Nephites and the modern US. In so doing, the narrative establishes a moral geography wherein inhabitancy in the land implicitly places people under covenant to follow God's laws. In this regard, we can think of the Hill Cumorah as space both sacred and sacralising – as sacralising space which 'sets apart' the US in a way which may now seem overly local for an internationalising faith.